2020
DOI: 10.18203/2349-3291.ijcp20200689
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hyponatremia and its utility as an indicator of morbidity in children hospitalised with community acquired pneumonia

Abstract: Background: The aims of the study were to determine the incidence of hyponatremia associated with pneumonia and to assess its utility as an indicator of morbidity in children hospitalized with community acquired pneumonia between 2 months and 5 years of age.Methods: This was a prospective study of children aged 2 months to 5 years hospitalized with community acquired pneumonia. 120 children aged 2 months to 5 years with symptoms of lower respiratory tract infection and had radiological evidence of pneumonia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Glatstein et al 23 reported a strong correlation between the consolidation of lung and hyponatremia, and a similar finding was reported by Natarajan et al 24 in a prospective observational study conducted in the southern part of India. A similar correlation between the consolidation of the lung on CT Chest and the presence of hyponatremia was observed in our study.…”
Section: Discussionsupporting
confidence: 69%
“…Glatstein et al 23 reported a strong correlation between the consolidation of lung and hyponatremia, and a similar finding was reported by Natarajan et al 24 in a prospective observational study conducted in the southern part of India. A similar correlation between the consolidation of the lung on CT Chest and the presence of hyponatremia was observed in our study.…”
Section: Discussionsupporting
confidence: 69%